An integrated PLS-SEM model on the interplay of antecedents and moderators driving corporate entrepreneurship activity in South Africa - Boris Urban; Thanusha Govender (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: Corporate entrepreneurship (CE) is a multi-faceted phenomenon, and although there is extant research on CE, there are knowledge gaps that warrant a deeper understanding. Indeed, focusing solely on independent variables overlooks the extent to which CE activities are mutually and reciprocally supportive. We align our article with research calls for theory building, which provides a novel understanding of the dynamic complexity of the CE process. METHODOLOGY: In this regard, we formulate and empirically evaluate an integrated CE model that reflects the integrative complexity of the antecedents driving CEA. The study context is the South African banking sector, where primary data (n = 312) is obtained via a structured survey. Four meta-hypotheses and several sub-hypotheses, reflecting the organizational, individual, and environmental level antecedents, are tested using partial least squares structural equation modeling (PLS-SEM). FINDINGS: The main study finding validates that corporate strategy is the bedrock of CEA. The results also reveal that entrepreneurial strategy, entrepreneurial structure, transformational leadership, organizational resources, and an entrepreneurial mindset are significant predictors of CEA. IMPLICATIONS: Practical implications highlight that it is important for managers to consider the configuration of the predictors within the CE model, which function as pathways to entrepreneurial corporate strategy. ORIGINALITY AND VALUE: Our study makes a unique contribution by developing and testing an integrated and comprehensive model reflecting the dynamic complexity of the antecedents driving CEA. It is anticipated that the results will allow researchers to compare and examine comparable antecedents to CEA and their applicability in global country contexts.